2010
DOI: 10.3109/03014460903508520
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase Omega class (GSTO) polymorphisms in a sample from Rome (Central Italy)

Abstract: Glutathione S-transferases are a superfamily of enzymes that are involved in biotransformation of drugs, xenobiotics and play a fundamental role in the protection of cells from oxidative stress. In humans, the recently described GST Omega class contains two expressed genes GSTO1 and GSTO2, located on chromosome 10 (10q24.3). Four polymorphisms in GSTO genes have been identified in ethnic groups: GSTO1*A140D (rs4925), GSTO1*E155del (rs56204475), GSTO1*E208K (rs11509438) and GSTO2*N142D (rs156697). This study pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
11
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 14 publications
6
11
0
Order By: Relevance
“…Glutathione S-transferases (GSTs; EC: 2.5.1.18) comprise a superfamily of genes encoding enzymes that are very important in the clinical outcome of different multifactorial diseases [14][15][16]. These enzymes are involved in metabolic detoxification of reactive electrophiles, in biosynthesis of leukotrienes, prostaglandins, testosterone, and progesterone, and in the degradation of tyrosine [17,18]. Over the last two decades, a significant body of data has been accumulated linking genetic variability of GSTs with the development and expression of several multifactorial diseases [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Glutathione S-transferases (GSTs; EC: 2.5.1.18) comprise a superfamily of genes encoding enzymes that are very important in the clinical outcome of different multifactorial diseases [14][15][16]. These enzymes are involved in metabolic detoxification of reactive electrophiles, in biosynthesis of leukotrienes, prostaglandins, testosterone, and progesterone, and in the degradation of tyrosine [17,18]. Over the last two decades, a significant body of data has been accumulated linking genetic variability of GSTs with the development and expression of several multifactorial diseases [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of GSTO1 A140D seems to vary between races (9,(11)(12)(13)(14)(15)(16)(17)(18), but only a few studies investigated this frequency in Caucasians (9,14,17,18). In the single study of GSTO1 A140D that included the Turkish population, Takeshita et al (17) observed that its distribution differed from Caucasian populations, and was more similar to African, Eastern Asian, and Brazilian populations.…”
mentioning
confidence: 99%
“…Information about the classification of these human groups and DNA extraction procedures is available through previous studies. [18][19][20][21] We exported additional data from the databases of HapMap and 1000 Genomes Projects. 22 …”
Section: Materials and Methods Samplesmentioning
confidence: 99%